1991
DOI: 10.1200/jco.1991.9.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of tumor cell ploidy and N-myc gene amplification in childhood neuroblastoma: a Pediatric Oncology Group study.

Abstract: We assessed tumor cell DNA content (ploidy) and N-myc gene copy number as predictors of long-term disease-free survival in 298 children with neuroblastoma. Diploid tumor stem lines were identified in 101 patients (34%), clonal hyperdiploid abnormalities in 194 (65%), and hypodiploid stem lines in three (1%). In children with widely disseminated tumors at diagnosis (stage D), ploidy had a highly age-dependent influence on prognosis. Among infants (less than 12 months) treated with cyclophosphamide-doxorubicin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
290
1
8

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(312 citation statements)
references
References 38 publications
13
290
1
8
Order By: Relevance
“…As amplification of the MYCN oncogene is an important prognostic factor in neuroblastoma (Look et al, 1991), we tested neuroblastoma cells with different MYCN status. COX inhibitors were able to induce dosedependent inhibition of cell growth in both MYCN amplified (IMR-5) and non-amplified (SK-N-AS, SK-N-SH, SH-SY5Y, SH-EP) neuroblastoma cell lines (Figure 1).…”
Section: Neuroblastoma Is Sensitive To Cox Inhibitorsmentioning
confidence: 99%
“…As amplification of the MYCN oncogene is an important prognostic factor in neuroblastoma (Look et al, 1991), we tested neuroblastoma cells with different MYCN status. COX inhibitors were able to induce dosedependent inhibition of cell growth in both MYCN amplified (IMR-5) and non-amplified (SK-N-AS, SK-N-SH, SH-SY5Y, SH-EP) neuroblastoma cell lines (Figure 1).…”
Section: Neuroblastoma Is Sensitive To Cox Inhibitorsmentioning
confidence: 99%
“…1,2 A number of prognostic parameters for the disease have been identified, including age, loss of heterozygosity at chromosome 1p36, DNA ploidy, histopathologic stage and amplification of the N-myc proto-oncogene. [3][4][5][6][7][8] The latter condition is strongly correlated with advanced disease, insensitivity to chemotherapy and poor outcome. 9 -12 N-myc and other members of the myc family encode transcription factors that control the expression of genes involved in cell growth, differentiation and survival.…”
mentioning
confidence: 99%
“…Endoreduplication would lead to an apparent increase in either the cut or uncut allele in tumour DNA compared with normal DNA, as we observed. Indeed, an extra chromosome 5 has been noted to occur in several neuroblastoma karyotypes (Kaneko et al, 1987;Hayashi et al, 1989;Look et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In 1983, Schwab et al determined that a gene termed N-myc, related to the protooncogene c-myc, was amplified in many human neuroblastoma cell lines (Schwab et al, 1983). Subsequent studies have shown that DNA amplification of this gene, found in about 25% of neuroblastomas, is associated with rapid progression of disease (Seeger et al, 1985;Look et al, 1991;Fong et al, 1992). In one study of neuroblastoma, DNA content, which grossly reflects chromosome number, was diploid (DNA index= 1) in 44%, near-diploid (DNA index 1.18) in 6%, near-triploid (DNA index= 1.25-1.68) in 48% and hypotetraploid (DNA index= 1.85) in 2% of 59 neuroblastoma tumours analysed (Bourhis et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation